2016
DOI: 10.1590/0102-33062016abb0036
|View full text |Cite
|
Sign up to set email alerts
|

Using ecological niche models to predict the impact of global climate change on the geographical distribution and productivity of Euterpe oleracea Mart. (Arecaceae) in the Amazon

Abstract: We assess the impact of climate change on the geographic distribution and productivity of Euterpe oleracea (Arecaceae), commonly called açaí. To construct the ecological niche model of E. oleracea, we used 95 points of occurrence, fi ve bioclimatic variables in current and future climate scenarios and Maxent software. Th e Akaike Information Criteria (AIC) was used to rank the ability of the models (considering ecological, socioeconomic and spatial variables) to explain the variation in productivity of E. oler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…These results need to be interpreted with caution, since all species that were predicted to lose 100% of BAH have small sample sizes (n < 50, Supplementary Table S1 ), which is one of the main determinants of model accuracy 51 . Some species tend to be favored by certain climate change scenarios under full dispersal scenario 52 , 53 , such as here the medicinal species Varronia curassavica , with an increase of BAH up to 230%; the ornamental species Epidendrum fulgens up to 264% and the forage species Indigofera sabulicola up to 387%. Although some species were predicted to expand their range, this does not guarantee the survival of these species, since other drivers, such as the capability of poor dispersal species to cope with climate change 54 , deforestation 44 , 55 and other land-use changes threaten Brazilian ecosystems and the survival of their associated species 56 .…”
Section: Discussionmentioning
confidence: 99%
“…These results need to be interpreted with caution, since all species that were predicted to lose 100% of BAH have small sample sizes (n < 50, Supplementary Table S1 ), which is one of the main determinants of model accuracy 51 . Some species tend to be favored by certain climate change scenarios under full dispersal scenario 52 , 53 , such as here the medicinal species Varronia curassavica , with an increase of BAH up to 230%; the ornamental species Epidendrum fulgens up to 264% and the forage species Indigofera sabulicola up to 387%. Although some species were predicted to expand their range, this does not guarantee the survival of these species, since other drivers, such as the capability of poor dispersal species to cope with climate change 54 , deforestation 44 , 55 and other land-use changes threaten Brazilian ecosystems and the survival of their associated species 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Current abiotic conditions act like filters delimiting boundaries to the distribution of these taxa, but climate change effects could weaken such filters for aquatic invasive species (Rahel and Olden 2008). Nevertheless, the overall expansion of environmental adequacy does not necessarily translate into an organisms’ ability to occupy new climatically available areas, as other local forces might interact compromising dispersion (Vaz and Nabout 2016). VanDerWal et al (2013) draw attention to the complexity of the combined climate change impacts and other factors influencing species distribution in a way so that simply looking at the expected poleward shift in biodiversity geographic distribution, detrimental to climate change underestimates the real effects of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of plants have demonstrated a reduction in the potential geographical distribution for future scenarios (Collevatti et al 2011;Mendoza-González et al 2013). However, some species show the opposite, such as Euterpe oleracea (Arecaceae), which presented an increased distribution in future scenarios, although relatively small (Vaz & Nabout 2016); this can be attributed to environmental and physiological plant variables.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, climate change can increase, reduce, or displace the geographic distribution of species until new areas become climatically suitable or available. The geographic distribution of species is a measure frequently evaluated in studies on global warming (Vaz & Nabout 2016), and many recent studies have used ecological niche models to evaluate the impact of global climate change on species distribution (see Peterson et al 2011;Nemésio 2016;Lamsal et al 2018;Faleiro et al 2018).…”
Section: Introductionmentioning
confidence: 99%